Rediscoveries, lectotypifications and new species record of the genus Saurauia (Actinidiaceae) from southwestern Philippines - Mazo, Kean Roe F.; Aribal, Lowell G. (Phytotaxa, 2025)
Fieldwork in Zamboanga Peninsula in 2021 resulted in the recollection of endemic Saurauia species. After thorough morphological analysis, the two specimens having cauliflorous inflorescences were identified as Saurauia denticulata and S. zamboangensis, both endemic to Zamboanga Peninsula, while the specimen with axillary inflorescence matched with S. merrillii, a species recorded in the islands of Leyte and Samar so far. Here, we provided amended descriptions of the three Saurauia species and designated lectotypes for S. merrillii and S. zamboangensis. Colored photographs, ecological notes, and provisional IUCN conservation assessments of the three species are also provided.